The Falls In Care Home study: a feasibility randomized controlled trial of the use of a risk assessment and decision support tool to prevent falls in care homes - Walker, Gemma M.; Armstrong, Sarah; Gordon, Adam L.; Gladman, John R.F.; Robertson, Kate; Ward, Marie; Conroy, Simon; Arnold, Gail; Darby, Janet; Frowd, Nadia; Williams, Wynne; Knowles, Sue; et al. (SAGE, 2015)
Objective: To explore the feasibility of implementing and evaluating the Guide to Action Care Home fall prevention intervention.